Koordinasi Badan Penanggulangan Bencana Daerah (BPBD) Dengan Dinas Pekerjaan Umum Dalam Upayapenanggulangan Pasca Bencana Banjir Di Kota Medan - Cindy Monica; Siti Hazzah Nur R. (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
Regional Disaster Management Agency as an agency formed by the government as a forum for disaster management. One of the actions taken by BPBD to cope with flood disasters is through coordination with the Medan City Public Works Department. This study aims to describe the coordination between BPBD and the Medan City Public Works Agency in post-flood disaster management in Medan City including the stages of rehabilitation and reconstruction. The research method used is descriptive qualitative research, while the data collection techniques used are observation, interviews and documentation. The results of the study indicate that the coordination between BPBD and the Public Works Agency in the post-flood disaster implementation in Medan City has not been maximized.